Kinerja Guru SMPN 1 Rantau Selamat Meningkat Melalui Supervisi Manajerial Administrasi - Muhammad Nasir (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The issues raised whether with implemented managerial supervision will be able to improve the teachers’ quality of SMP N 1 Rantau Selamat. This study aimed to determine the quality improvement of teachers SMP N 1 Rantau Selamat through the implementation of supervision. This study is a School Action Research (PTS) using a qualitative approach implemented over 2 cycles. Duration of 3 months study from January to March 2017. The subjects of this study were 4 teachers. The research procedure is a cycle that each cycle consists of planning, implementation, observation, and reflection. Data collection tools are observation sheets and field notes. Data collection techniques with observation and field notes. Data analysis was performed on teacher performance and field notes. The results of the first cycle of the study of managerial administrative value of teachers ranged from 3.2 to 3.7 with good and sufficient categories. Classically, the average value obtained is 3.0 or 69%. The number of teachers who have met the criteria of administrative managerial success is only 2 people or 50%. With a percentage less than 75 (percentage ≤ 75). In cycle II, the acquisition of managerial administrative value reaches the expectation of research. The four subjects received a value greater than or equal to 3.4 (value ≥ 3.4). The value achieved between 3.5 - 4.6 is good and very good category. Teacher performance effectiveness in cycle II has reached 100%. 100% effectiveness meets the criteria of classical effectiveness (effectiveness ≥ 75% in class). The average value of the overall teacher managerial aspect / component acquired is 3.9.